Peran kedisiplinan siswa dalam membaca al-Qur'an dan literasi sebelum memulai pembelajaran - Ariffani, Khairunnisa nisa (Maliki Interdisciplinary Journal, 2024)
Maintaining student discipline is crucial to helping pupils become literate in the Al-Qur'an. This essay investigates the connection between students' self-discipline in reading the Qur'an and their pre-learning literacy development. The need of equipping students to become proficient and discerning Qur'anic readers is underscored by this study, which incorporates an organized method of studying the Qur'an and fosters student discipline. The impact that students' discipline in reading the Koran had on their literacy skills was investigated using qualitative research methods. The results indicate that kids who study the Koran with a high degree of discipline typically have higher literacy levels than students who read it with a lower degree of discipline. In addition, this essay addresses how educators and the classroom may help students maintain self-control and become literate in the Al-Qur'an. The creation of teaching methods that promote student self-control and the inclusion of Al-Qur'anic literacy in the curriculum are two examples of the research's practical applications. To sum up, students' commitment to reading the Qur'an is crucial to developing their literacy, which is a prerequisite for beginning more in-depth study.